The Function and Evolution of Variable Repetitive Protein Domains - Stewart, Taylor. (Tufts University. Tisch Library., 2021)
Thesis (Ph.D.)--Tufts University, 2021.; Submitted to the Dept. of Biology.; Advisor: Stephen Fuchs.; Committee: Mitch McVey, Benjamin Wolfe, and Justin Hines.; Keywords: Molecular biology, and Genetics.; Repetitive protein domains were historically dismissed as functionally unimportant due to their lack of a stable three-dimensional structure. More recently, these domains have been revealed to be important for activities such as binding, signaling, phase separation, and prion formation. The DNA encoding repeat domains is frequently unstable resulting in copy number variation, and this variation impacts protein function in many cases. Variable protein repeats serve as modulators of protein function across different timescales, with phase separation regulating function during the lifespan of a cell, prionogenesis conferring phenotypes across generations, and copy number variability promoting protein function evolution. The study of repeats and their role in each of these biological processes, as well as the effects of variation is still in its infancy. The work outlined in this thesis utilizes the model organism S. cerevisiae to explore two questions: 1) What are the genetic mechanisms that underlie repeat variation? 2) What is the role of variable repeats in transcription? To address the first question, the repetitive C-terminal domain of RNA Polymerase II was used to probe the mechanism(s) of microsatellite instability. Contractions of this domain were found to be mediated by template switching during post- replication repair. This study revealed the role of secondary structures and microhomologies in microsatellite instability. To address the second question, the naturally variable polyasparagine domain of the transcription factor Azf1p was investigated. Deletion of this domain impacts gene expression as well as growth on different carbon sources, highlighting a potential for repeat domains as tunable transcriptional regulators during fermentation and small molecule production applications. Future directions of study are also discussed, and several specific approaches that can be taken to continue advancing research in this field are proposed.